(untitled) (Vietnam Journal of Community Medicine, 2024)
The diagnosis of pulmonary tuberculosis (PTB) in children is challenging. Difficulties in acquiring suitable specimens, pauci-bacillary load, and limitations of current diagnostic methods often make microbiological confirmation difficult. Chest - Xrays (CXRs) provides an additional diagnostic modality that is frequently used in clinical practice. Furthermore, CXR can help choose treatment regimen for non-severe cases.